An integrated multi-objective mathematical programming and simulation model for a multi-layer facility location problem. (6th October 2021) - Attari, Mahdi Yousefi Nejad; Ala, Ali; Kolahi-Randji, Saeed; Jami, Ensiyeh Neishabouri
Multi-layer facility location problems deal with providing service to customers in different layers. In the context of system performance and complexity, all the needed services of a customer that is entered to a system should be met and we suppose that the customer will remain in the system until the last layer. In this study, we present an integrated methodology for a multi-layer facility location problem considering the congestion in it using queuing theory which is highly used for modelling complex systems. An integrated multi-objective mathematical programming and simulation model under fuzzy environment and minimising the travel times between the layers and waiting time in server queues in healthcare blood chain is proposed. Discrete-event simulation model in Arena software is used to solve the model with respect to their efficiency in dealing with complexity of multi-layer systems. A numerical example including four different scenarios is tested for the proposed method. Results show that fourth scenario is better than others in context of the external sources needed to add to facilities in layers and it also decreases the waiting time to roughly 50%.